Case report: A rare case of catastrophic Takayasu arteritis: acute ischemic stroke and anterior ischemic optic neuropathy - Oladotun V. Olalusi; Oladotun V. Olalusi; Joseph Yaria; Akintomiwa Makanjuola; Rufus Akinyemi; Rufus Akinyemi; Rufus Akinyemi; Mayowa Owolabi; Mayowa Owolabi; Mayowa Owolabi; Mayowa Owolabi; Mayowa Owolabi; et al. (Frontiers in Stroke)
Acute ischemic stroke (AIS) is a known complication of Takayasu arteritis (TAK); however, it is infrequently the first symptom observed. There have been no reports of concomitant AIS and anterior ischemic optic neuropathy (AION) as an initial manifestation of TAK. We present a case of TAK causing stroke and painless vision loss in a young Nigerian woman. A 33-year-old female patient presented with abrupt onset weakness in the right extremities and painless vision loss in her left eye. Her medical history included joint pain, malaise, syncope, and dizziness, along with peripheral vascular collapse, requiring recurrent hospital admissions. She had an absent left radial pulse, reduced left carotid pulse, and unrecordable blood pressure in her left arm. There was a relative afferent pupillary defect (RAPD), with fundoscopy findings indicating optic disc pallor. She had expressive aphasia, right facial paresis, and right flaccid hemiparesis. Brain computed tomography (CT) showed an infarct in the left middle cerebral artery (MCA) territory. The brain CT angiography showed diffuse enhancing aortic arch wall thickening and multiple aortic arch branch obstructive disease. The diagnosis was TAK complicated by left hemispheric infarctive stroke and left AION. She began treatment with prednisolone, azathioprine, and secondary stroke preventive care. Her vision improved to the ability to count fingers, with good functional outcomes and reduced disease activity. This case highlights the challenging diagnostic trajectory of TAK in a Nigerian female patient, featuring a unique multi-vessel affectation. Clinicians should be aware of the protean clinical presentations of TAK to reduce adverse cardiovascular complications.